2017
DOI: 10.3748/wjg.v23.i45.8062
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination therapy with natriuretic and aquaretic drugs in cirrhotic ascites patients: A randomized study

Abstract: AIMTo assess the effects of a combination therapy with natriuretic and aquaretic drugs in cirrhotic ascites patients.METHODSA two-center, randomized, open-label, prospective study was conducted. Japanese patients who met the criteria were randomized to trial group and the combination diuretic group (received 7.5 mg of tolvaptan) or the conventional diuretic group (received 40 mg of furosemide) for 7 d in addition to the natriuretic drug which was used prior to enrolment in this study. The primary endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…This rationale is justified as the higher doses of conventional diuretics can cause ADRs such as renal impairment [7]. Instead, adding tolvaptan to a treatment regimen seems to be a better option than using conventional diuretics; tolvaptan does not seem to impair renal function in clinical practice [19][20][21], thereby reducing the ADRs in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This rationale is justified as the higher doses of conventional diuretics can cause ADRs such as renal impairment [7]. Instead, adding tolvaptan to a treatment regimen seems to be a better option than using conventional diuretics; tolvaptan does not seem to impair renal function in clinical practice [19][20][21], thereby reducing the ADRs in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…And, the occurrence rates of total adverse events, diarrhea and frequency of urination were evaluated under different dose. 5 studies report the total incidence of adverse events (including 620 patients) in the intervention process [16][17][18][19][20]. Mate analysis result shows that in the intervention process, the total incidence of adverse events was obviously higher than that of traditional diuretic group (OR=1.98, 95%CI [1.11, 3.52], P=0.02, Fig 5A).…”
Section: Safetymentioning
confidence: 99%
“…In the aspect of minor indexes, the changes in the average weight, average waistline and average ascites amount are reported in 4 studies (499 patients) [17][18][19][20], 3 studies (440 patients) [17][18]20], and 2 studies (216 patients) [17,19], respectively. The changes of urine volume on the first day of intervention compared with the last day are reported in 4 studies (498 patients) [16][17][19][20][21]. After the intervention for 7 days, the reduction of average weight (WMD=-1.51Kg, 95%CI [-1.86, -1.16], P<0.001, Fig 2A), average abdominal girth (WMD=-2.05cm, 95%CI [-2.67, -1.43], P<0.001, Fig 2B), and the average ascites amount (WMD=-293.43mL, 95%CI [-502.53, -84.34], P=0.006, Fig 2C) of combined diuretic group was obviously better than that of traditional diuretic group.…”
Section: Study Screening and Bias Analysismentioning
confidence: 99%
“…Additionally, a phase 2 trial has shown that tolvaptan significantly reduced the body weight and abdominal circumference compared to placebo in patients with liver cirrhosis‐associated ascites . Another randomized trial showed that a combination of conventional natriuretic drugs and tolvaptan was superior to conventional therapy alone in cirrhosis‐associated ascites …”
Section: Management Of Portal Hypertension In Pldmentioning
confidence: 99%
“…58 Another randomized trial showed that a combination of conventional natriuretic drugs and tolvaptan was superior to conventional therapy alone in cirrhosis-associated ascites. 59 Two recent case reports have suggested that tolvaptan may also reduce liver volume. 60,61 The potential effect was corroborated by an in vitro study that showed involvement of vasopressin in liver cyst growth.…”
Section: Management Of Ascitesmentioning
confidence: 99%